Reliability and Construct Validity of the Portuguese Version of the Changes in Sexual Functioning Questionnaire - Short-Form (CSFQ-14) and Its Association with Subjective Sexual Well-being - , Henrique Pereira; , Samuel Monteiro; , Graça Esgalhado; , Rosa Marina Afonso; , Manuel Loureiro (Archives of Current Research International, 2016)
Background: The psychometric properties of an instrument should be evaluated routinely when using different samples. This study evaluated the psychometric properties of the Changes in Sexual Functioning Questionnaire - Short-Form (CSFQ-14) in order to validate it when applied to a sample of Portuguese participants. Methods: Confirmatory factor analysis (CFA) was conducted the ratio chi-square by degrees of freedom (χ2/df). The comparative fit index (CFI), the Tucker-Lewis index (TLI), and the root mean square error of approximation (RMSEA) as indices. The sample consists of 1.416 Portuguese adults with a mean age of 38.74 years (SD = 13.63). Participants completed the Changes in Sexual Functioning Questionnaire-Short Form (CSFQ-14) and the "Subjective sexual well-being" questionnaire. Results: Levels of sexual functioning among our sample were found to be moderately high. CFA showed that the factor structure of the CSFQ-14 was satisfactory fit to the sample (λ = .40 to .88; χ2/df = 4.426. CFI = .914. TLI = .905. RMSEA = .095). The correlation matrix between the CSFQ-14 and the items of the Subjective Sexual Well-being items demonstrated that there were high correlations between all variables. Conclusion: The CSFQ-14 was found to be a valid and reliable assessment of sexual-related quality of life in anon-clinical Portuguese sample.